2009
DOI: 10.1007/s00586-009-1005-x
|View full text |Cite
|
Sign up to set email alerts
|

The patient’s perspective on complications after spine surgery

Abstract: Recent years have witnessed a paradigm shift in relation to the assessment of outcome in spine surgery: multidimensional patient-centred questionnaires have superseded traditional surgeon-based ratings of outcome, and surgical registries have been developed to capitalise on the principle of ''strength in numbers.'' However, the assessment of complications has not enjoyed this same enlightened patient-centred approach. The present study investigated post-surgical complications from the patient's perspective. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 18 publications
4
20
0
Order By: Relevance
“…The influence of the specific design of prosthesis should also be further investigated; in the present study, all types of prostheses were examined as one group and compared with all techniques of fusion-a possible limitation from the scientific methodology point of view, but a pragmatic approach that ideally reflected the everyday practice of a large Spine Center. Our data on patient self-assessed re-operation rates and complications after surgery-a relatively new concept in the field of outcomes research, and one that reveals some startling results [23]-suggested slightly more favourable results in the arthroplasty group, especially by 2 years FU; however, the group sizes were too small for meaningful statistical analyses of the data. Again, observational studies, using the data collected in large-scale registries such as the European Spine Tango, are well disposed to address some of these issues and to complement the findings of the RCTs.…”
Section: Discussionmentioning
confidence: 70%
“…The influence of the specific design of prosthesis should also be further investigated; in the present study, all types of prostheses were examined as one group and compared with all techniques of fusion-a possible limitation from the scientific methodology point of view, but a pragmatic approach that ideally reflected the everyday practice of a large Spine Center. Our data on patient self-assessed re-operation rates and complications after surgery-a relatively new concept in the field of outcomes research, and one that reveals some startling results [23]-suggested slightly more favourable results in the arthroplasty group, especially by 2 years FU; however, the group sizes were too small for meaningful statistical analyses of the data. Again, observational studies, using the data collected in large-scale registries such as the European Spine Tango, are well disposed to address some of these issues and to complement the findings of the RCTs.…”
Section: Discussionmentioning
confidence: 70%
“…Reports of the clinical outcome of geriatric patients (>80 years of age) who have undergone lumbar fusion are particularly rare. Patient-reported outcome measures help avoid bias in the reporting of surgical success [11][12][13] and provide an important insight into the impact of surgery from the patient's perspective 14 , allowing the collection of quantitative data regarding pain, function, and health-related quality of life 15 .…”
Section: Introductionmentioning
confidence: 99%
“…4,[7][8][9][10] Reports of the clinical outcome of geriatric patients (>80 years of age) who have undergone lumbar fusion are particularly rare. Patientreported outcome measures help avoid bias in the reporting of surgical success [11][12][13] and provide an important insight into the impact of surgery from the patient's perspective, 14 allowing the collection of quantitative data regarding pain, function, and health-related quality of life (QoL). 15 The aim of this study was to compare patient-rated outcome, complication rates, and length of hospital stay (LOS) among groups of younger (!50 years <65 years), older (!65 years <80 years), and geriatric (!80 years) patients undergoing lumbar fusion for degenerative disease.…”
mentioning
confidence: 99%